COASTAL CLIFF INSTABILITY, A CASE STUDY FROM THE UK - Saroglou, C.; Alexandrou, D. (Bulletin of the Geological Society of Greece, 2016)
The present paper presents the conceptual ground model for coastal cliff retreat and instability. Cliff instability has been intensified due to climate change in the last years, especially by sea level change and high windstorms. A case study ofcliff instability in the SW coast in the UK is presented. The stability of the cliffs is primarily controlled by the presence of tensile cracks parallel to the cliff face and intersecting fractures as well as undercutting of cliff base due to wave action. The cliff instability mechanisms were identified for different locations along the shoreline and the cliffs were classified according to the cliff behaviour unit approach.